Strategi Writing to Learn pada Pembelajaran IPA SMP untuk Meningkatkan Penguasaan Konsep dan Keterampilan Komunikasi Siswa pada Materi Tata Surya - Rita Sintiawati; Parlindungan Sinaga; Saeful Karim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The study of science is one of the important learning that activates and improves student competence, such as higher-order thinking and communication competency. The development of the ability to work scientifically and pursue the student to communicate investigation result are the main goal of science learning. Based on the previous study, the understanding of concept and student communication skills remains low at science learning. The learning strategy “writing to learn” is predicted to raise the low understanding concept ability and communication skill, especially in solar system learning material. The study aims to know the enhancement and get the prediction between the understanding of concept and communication skills after applying the strategy writing to learn in solar system material. The research used a quasi-experiment method with pre-experimental with one group pretest-posttest design. The study conducted in one of the junior high schools in Bandung, West Java. The instrument used is to measure the understanding of the concept by using multiple-choice questions, on the other hand, to measure the communication skill, the author use journal writing assignment. The analysis result showed that the implementation of writing to learn strategy improve the understanding of concept and communication skill even though it classified as a medium category. The enhancement happened toward the average communication skill in each meeting. Nonetheless, the low relation and influence are shown after correlation analysis happened between the understanding of concept and communication skills Keywords : Writing to Learn, Mastery of Concept, Communication Skills, Solar System Learning Material Tujuan dari penelitian ini adalah untuk mengetahui peningkatan serta mendapatkan gambaran hubungan antara kemampuan penguasaan konsep dan keterampilan komunikasi setelah diterapkannya strategi pembelajaran writing to learn, khususnya pada materi tata surya. Penelitian ini menggunakan metode quasi experiment dengan pre-experimental with one group pretest-posttest design dan dilaksanakan pada salah satu SMP di Kota Bandung, Jawa Barat. Instrumen yang digunakan untuk mengukur penguasaan konsep menggunakan soal tes pilihan ganda dan untuk mengukur keterampilan komunikasi menggunakan tugas menulis jurnal. Hasil analisis menunjukkan bahwa penerapan strategi writing to learn meningkatkan penguasaan konsep dan keterampilan komunikasi walaupun tergolong kategori sedang. Peningkatan pun terjadi terhadap rata-rata keterampilan komunikasi pada setiap pertemuannya. Walaupun demikian, hubungan dan pengaruh yang lemah ditunjukkan setelah analisis korelasi dilakukan antara penguasaan konsep dengan keterampilan komunikasi.Kata kunci: Writing to Learn, Penguasaan Konsep, Keterampilan Komunikasi, Tata surya